Core Competencies in the Professional Practice of the Library and Information Science Programme - Duran-Riquelme, A (IOS PRESS, 2024)
A professional practice is a type of internship, a practicum, that encompasses a supervised hands-on training experience for students to develop and identify the core and enabling competencies required in a professional environment. It also allows them to identify the developed and underdeveloped skills that are important in the labour environment while still undergoing an academic training. Therefore, the purpose of this research is to determine the core and enabling competencies required and developed by the students coursing the Library and Information Science Programme at Universidad Tecnologica Metropolitana during their professional practices carried out from 2019 through 2021. To this end, a questionnaire with open and closed-ended questions was used as data collection instrument. It was applied to a sample of 64 graduates from this Programme, out of a universe of 70 students in addition to a focus group to delve deeper into the answers obtained. The results established that both core and enabling competencies had been relevant in their professional practice. The most relevant core competencies were those related to information and knowledge services; information analysis and data retrieval; and organisation of data, information and knowledge assets meanwhile the most relevant enabling competencies were communication, teamwork and adaptability.